Causes and risk factors associated with pre-weaning calf mortality in dual-purpose cattle herds in Colima, Mexico - García-Márquez, Luis J. (2023)
The aim of this study was to determine the causes and identify the risk factors associated with pre-weaning mortality in four dual-purpose bovine herds in Colima, Mexico. Four herds were selected and births and deaths were recorded for 12 months. Information was collected on the calving number of the dam and the sex of the calf. Necropsy was performed in cases of death. Data were analyzed using the Chi-square test and logistic regression. The pre-weaning mortality rate was 4.30%, with half of the deaths occurring within the first 48 hours after birth, especially due to dystocia (50%) and congenital abnormalities (25%). A significant association was found between herd mortality and the number of calving of the cow (p<0.05), but not with the sex of the calf. Calves born in herd C were 4.60 times more likely to die than those born in the other three herds, while calves born to multiparous dams had a 72% lower risk of death than those born to primiparous dams.